Color Properties and Antioxidant Capacity of Purple Sweet Potato (Ipomoea batatas L) Anthocyanin Co-pigmented with Green Tea Extract - Retno Yunilawati; . Yemirta (Current Advances in Chemistry and Biochemistry Vol. 2, 2021)
The color properties and antioxidant capacity of purple sweet potato anthocyanin co-pigmented with green tea extract were investigated. The co-pigmentation process was done using green tea extract with varying concentration of polyphenol (2.5%; 5%; 7.5% and 10% b/v). The co-pigmentation of purple sweet potato anthocyanin with green tea extract could enhance the color intensity which was observed through the hyperchromic effects and bathochromic shifts. The co-pigmentation was optimal using the 5% of polyphenol concentration, where the bathochromic shifts (??max) was 4 nm and the hyperchromic effects (?A) was 0.565. The color observed with the CIELAB system showed that the co-pigmentation decreased the lightness (L*) value and increase the a* value. The result of antioxidant capacity assessment showed that the purple sweet potato anthocyanin co-pigmented with green tea extract has higher the antioxidant capacity than without co-pigment. Besides increased the color intensity, the co-pigmentation of the purple sweet potato anthocyanin with green tea extract also could increase the antioxidant capacity. This co-pigmentation was prospective to developed in the production of the anthocyanin from purple sweet potato with attractive color and high antioxidant capacity.